Lapatinib-loaded nanocolloidal polymeric micelles for the efficient treatment of breast cancer - Gunjan Vasant Bonde&, Gufran Ajmal&, Sarita Kumari Yadav&, Pooja Mittal&, Brahmeshwar Mishra (Journal of Applied Pharmaceutical Science, 2020)
This study aims at preparing and evaluating lapatinib-loaded polymeric micelles for the better treatment of breast cancer (BC). LP-loaded polymeric micelles (LP-PMs) were prepared as per our previous studies by using Soluplus® as the polymer. Therefore, we employed the lyophilization technique using mannitol as a cryoprotectant and further conducted in vitro and in vivo anticancer efficacy studies, in addition to our previously reported works. We found that the lyophilized LP-PMs were sufficiently stable and retained encapsulated drugs. Furthermore, their smooth surface was visualized on the atomic force microscopy. The X-ray powder diffractogram of LP-PMs showed successful encapsulation of Lapatinib; however, the presence of few drug molecules on the surface was evidenced by energy dispersive X-ray analysis. Furthermore, LP-PMs showed sustained release of drugs, with selective drug release in an acidic environment, resembling that of a tumor. The LP-PMs exhibited higher cytotoxicity against SKBr3 BC cells and also induced effective inhibition of the growth of the tumor in vivo when compared to that of lapatinib solution and marketed formulation. The results of this study indicate the greater potential of LP-PMs for the efficient treatment for BC.
Keywords: Anticancer agent, nanocarrier, passive targeting, polymeric micelles, SKBr3.